Particle laden flows around a circular cylinder from the hydrodynamic to granular regime - Schuster, D.; Climent, E.; Rüde, Ulrich (International Journal of Multiphase Flow, 2023)
The flow around a circular cylinder is studied with the presence of solid finite-size spherical particles. The simulations of suspension flows are based on highly efficient simulation algorithms to generate scalable Lattice Boltzmann Method calculations. Simulations of particle resolved dynamics with up to 4800 million grid cells and 1.8 million spherical particles are carried out for different flow regimes and particle concentrations (from dilute, 5% volume concentration to semi-dilute regime, 20%). We investigated a range of parameters that spans from suspensions of iso-dense particles to highly inertial particles in a granular flow, while considering particle to cylinder diameter ratios of 5 and 10. The flow response is described by characteristic properties such as vortex shedding frequency or wake recirculation length. Flow regimes with iso-dense particles can be rationalized by means of mixture material properties while we observe a progressive transition to granular flow for inertial particles. Drag and lift forces acting onto the cylinder are presented in time and frequency domains and the physical analysis is based on the respective hydrodynamic and particle collision contributions.
CRIS-Team Scopus Importer:2023-05-12
Keywords: Dispersed two phase flow; High performance computing; Lattice-Boltzmann method; Rigid body dynamics